2023
DOI: 10.1038/s41598-023-45139-7
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between glomerular endothelial cells and podocytes controls their responses to metabolic stimuli in diabetic nephropathy

Michael Albrecht,
Carsten Sticht,
Tabea Wagner
et al.

Abstract: In diabetic nephropathy (DN), glomerular endothelial cells (GECs) and podocytes undergo pathological alterations, which are influenced by metabolic changes characteristic of diabetes, including hyperglycaemia (HG) and elevated methylglyoxal (MGO) levels. However, it remains insufficiently understood what effects these metabolic factors have on GEC and podocytes and to what extent the interactions between the two cell types can modulate these effects. To address these questions, we established a co-culture syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Studies in cultured GECs may not accurately reflect the diabetic environment in vivo, and more complex cell culture models, e.g. co-culture of cell lines, may be required to address mechanistic questions [46]. Evaluation of iPLA2γ metabolic effects and autophagy in human diabetic kidneys is difficult, although autophagy genes and gene ontology pathways are upregulated in glomeruli in human diabetic nephropathy [47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cultured GECs may not accurately reflect the diabetic environment in vivo, and more complex cell culture models, e.g. co-culture of cell lines, may be required to address mechanistic questions [46]. Evaluation of iPLA2γ metabolic effects and autophagy in human diabetic kidneys is difficult, although autophagy genes and gene ontology pathways are upregulated in glomeruli in human diabetic nephropathy [47].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of studies in cultured GECs is that these cells may not accurately reflect diabetic nephropathy in vivo, and more complex cell culture models, e.g. co-culture of cell lines, may be required to address mechanistic questions 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study established a co-culture system of GECs and podocytes for gene expression analysis and found that both HG and methylglyoxal (MGO) led to the downregulation of genes related to ECM tissue in podocytes. Importantly, this downregulation depended on the cell-to-cell crosstalk between GECs and podocytes [ 128 ]. Notably, none of the identified genes were differentially expressed in single cultures of their respective cells, underscoring the critical role of cellular interactions between GECs and podocytes in the early development of DKD [ 128 ].…”
Section: The Pathological Crosstalk Among Podocytes Gecs and Mcs In Dkdmentioning
confidence: 99%
“…Importantly, this downregulation depended on the cell-to-cell crosstalk between GECs and podocytes [ 128 ]. Notably, none of the identified genes were differentially expressed in single cultures of their respective cells, underscoring the critical role of cellular interactions between GECs and podocytes in the early development of DKD [ 128 ].…”
Section: The Pathological Crosstalk Among Podocytes Gecs and Mcs In Dkdmentioning
confidence: 99%
See 1 more Smart Citation